The Special Precincts for Urban Redevelopment (SPURs) of Makati City, Metro Manila - Tomeldan, Michael V.; Abrera, Gino Bjorn A.; Diaz, Dennis Oliver S.; Dungca, Joana Lisa R.; Lejarde, Godesil G.; Melgazo, Dylan James L.; Orbon, Glenn T.; Tumambing, Mary Janessie T.; Vitug, Voltaire V. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 5, 2016)
Urban renewal is a strategy in revitalizing underutilized and degraded sections of the inner city in the hope of reducing crimes, enhancing the environment, preventing further depreciation of land values, and stimulating economic activity. Many urban renewal projects in the past, however, have been associated with massive demolition, displacement of residents, expensive infrastructure and gentrification of the urban renewal site. In Makati City, Philippines, urban renewal schemes are explored to determine the appropriate developments for identified urban renewal sites that are situated in the fringes of its affluent sections. The urban renewal proposals seek to involve the participation of the residents of the blighted areas so that they themselves can benefit from the renewal. The conceptualized “shared growth” urban renewal initiatives attempt to minimize dislocation, encourage investment, improve the urban environment, create a more vibrant neighborhood, and spread economic benefits to most of the existing residents of the redevelopment sites.